Study Effects of Nigella Sativa Seeds Oil in Some Physiological Parameters in Experimental Heart Failure Induced by Ivabradine in Male Rats - Heba A. Abd-Alsalam Alsalame (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim of this study was to investigate the effects of Nigella Sativa Seeds oil In some physiological parameters against heart failure Induced By Ivabradine in rats .A total of 60 male rats were used in this experiment, the rats were divided into three groups: control rats (n = 20); IBD (n = 20); IBD+ N. sativa oil (n = 20). The first group (G1) was a control group. The second group (G2) was given 10 mg/kg of IBD, while the third group (G3) was injected with 10 mg/kgIBD + oral dosage of 2.5 mg/kg N. sativa oil for three months., after three months, the blood was withdrawn from the heart. to measure the concentration of ANP, BNP, NE, A-II, ALDO, ACE, MDA, SOD, TNF-? and IL-6 the Results revels that Levels of BNP, NE, MDA, IL-6 and TNF-?. were significantly increasead in G2 rats, with no significant difference was observed in ANP in rats in G2 compared to G1 rats . The level of ACE, A-II, SOD and ALDO in G2 rats had significantly decreased compared to that observed in G1 rats, oral administration of Nigella Sativa seeds oil (G3) showed no significant difference inANP, BNP, NE, A-II, ALDO, ACE, MDA, SOD, TNF-? and IL-6 compared with G1 group.